Profil Produksi Hijauan Rumput Gajah (Pennisetum purpureum) di Universitas Jember Kampus Bondowoso (Jurnal Peternakan Lingkungan Tropis, 2023)
This study aims to determine the profile of elephant grass production at different cutting ages, elephant grass productivity and forage capacity at the University of Jember, Bondowoso Campus. This study used the RAL method, with 3 treatments and 5 replications for each treatment at the cutting age of 40 days, 50 days and 60 days. Analysis used ANOVA diversity, further tests were carried out using DMRT. Parameters observed were characteristic profiles (plant height, number of leaves, leaf height, leaf width, number of tillers and fresh weight production), fresh production during the rainy season and livestock carrying capacity. The results showed that different cutting ages at the age of 60 days got the best results, namely plant height 425.90 cm, number of leaves 16.65 cm, leaf length 117.25 cm, leaf width 4.70 cm, and number of tillers 2.60 cm. Elephant grass production on livestock study program land during the rainy season at the age of 40 days was 8.38 tons/ha, 50 days old was 13.81 tons/ha and 60 days old was 14.58 tons/ha and the livestock population was 17.025 st.
Keywords: Array; Array; Array